NUMERICAL SIMULATION OF VISCOUS-INERTIAL LAMINAR SWIRLING FLOW IN A CIRCULAR TUBE WITH AN ECCENTRIC ROUND CORE - Sergey N. Kharlamov; Mehran Janghorbani (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
Relevance of the research is determined by the need to understand the features of hydrodynamics and heat exchange in reologically complex homogeneous and heterogeneous media during the flow in coaxial fields. This is important for making recommendations for drilling management, improving the reliability of special equipment at high dynamic and thermal loads during the rotation of the pipe, filling the inter-tube space with sludge, as well as establishing control over changes in composition, structure, pressure, velocity and rheophysical properties (at pseudo plastic, thixotropic and viscoelastic effects) of drilling mixture on horizontal areas of wells. Aims: to investigate the hydrodynamics of the viscous flow in coaxial tubes with eccentrically located round core, hollow channels at the conditions of direct and swirling (by the way of moving inner wall/locally at the entrance) streams; to explain the effects accompanying drilling at the sloping and horizontal sections of wells with eccentric drilling pipes; to establish the features of changes in the dynamic structure of the flow in the zones of motion of viscous media at the expense of inertial forces, as well as at the moments of flow braking when the section is cluttered by production products; to give recommendations on the beneficial effects of inertial forces on the viscosity of washing liquids to support effective oil drilling. Methodology: the engineering analysis of the reality models of transport processes of rheologically complex viscous media in internal systems (pipes, channels) and their description by the methods of physical, mathematical and numerical modeling in the form of systems of differential and algebraic equations, the solution of which in the most important aspects of drilling is consistent with the characteristics of special equipment elements. Results. The internal flows of viscous media with specific rheology (Newtonian and non-Newtonian fluids, such as Herschel–Bulkeley) have been investigated in geometric configurations typical of eccentric drilling pipes with effects from changes in their spatial orientation, flow rate, rotation intensity of the incoming flow/core wall, as well as rheophysical properties (τ0, κ, n). The parametric analysis of dynamic effects is performed for a range of criteria changes: Rossby Ro=0…5, Reynolds Re=102…103, Bingham Bi=5…15, eccentricity Δ=0,1…0,9. The effects of the mechanisms of convective-diffusion interaction of the momentum transfer process in pipes/channels at the complex flow movement and its contacts with walls are evaluated and generalized. Calculations show that any complications of the viscous flows are caused by changes in pressure, velocity, external and internal forces (due to the rheology). The features of the occurrence of recirculated zones at the swirling flow, fading along the length of the pipe of tangential velocity component, are analyzed. It is noted that with the growth of the core eccentricity the flow heterogeneity and the velocity vector axial component distribution asymmetry increase and the conditions to block the motion at the bottom of the inter-tube space are set. It was established that the presence of obstacles to flow movement in the coaxial fields, for example, in the form of sludge particles during drilling, can intensify the asymmetry of transfer processes, especially at high Reynolds (Re), Bingham (Bi) numbers. This can be avoided in flow regimes with the rotation of the drill pipe by the method of mobile wall/orbital movement. In conclusion, recommendations are given on modeling, calculating the flows of viscous media accompanying drilling, cleaning horizontal wells.